Edukasi pencegahan sikap konsumtif pada usia taman kanak-kanak - Surasman, Imelda Kartika; Ganlin, Fesya Devina Putri; Pradigdo, Randy Aprilino; Linawati, Nanik (Nur Science Institute, 2024)
Teaching children about finances at a young age is very important, during which the mind develops and an introduction to values ​​begins to form. Although some children at this age may not be familiar with such concepts, cultivating an understanding of the dangers of consumerism during critical developmental periods can provide long-term benefits. This community service activity is carried out to increase children's awareness of the attitudes children must have when facing the temptations of consumer life through puppet teaching media. The service method uses an interactive educational approach, and the stages include the preparation stage, implementation stage, and evaluation stage. Educational activities as part of this community service program positively impact children by increasing awareness and further understanding of the importance of frugal living and the evils of consumerism.